Financial Analysis of Sea Grape Cultivation (Caulerpa sp) Basic Plugging System Quadrant Net Method in Southeast Maluku Regency - Simon Marsholl Picaulima; Nally Yans Grispinomia Fraly Erbabley; Jane Lulinda Dangeubun; Dominggas Mintje Kelabora; Anggelina Amahorseja; Cenny Putnarubun; Frederika Pormes; Hamza Sedubun; Gracelia Masreng; Fitria Rahantan; Osama Yaurbulan (Faculty of Fisheries and Marine Science, Brawijaya University, 2023)
Sea grape cultivation (Caulerpa sp) is a fishery business activity that can increase the income of coastal communities; therefore, it is necessary to project profit and business opportunities in the future on an ongoing basis based on the profitability. This study aims to analyze the financial feasibility of sea grape (Caulerpa sp) cultivation with basic plugging system quadrant net method. This study used survey research methods, the type of data needed is primary and secondary data, data collection used a purposive sampling technique, and data collection used a triangulation method. Data analysis consists of total production costs, revenue, profit, break-even point and R/C ratio. The results of the financial analysis of the sea grape cultivation business (Caulerpa sp) using the quadrant net step-by-step system method show that the total production cost is IDR 3,368,333/year, business revenue is IDR 12,600,000/year, the business owner's profit is IDR 9,231,667/year, R/C ratio is 3.74, BEP (unit) is 21 kg and BEP (sales) is IDR 317,106. Sea grape cultivation (Caulerpa sp) with basic plugging system quadrant net method is financially feasible to be developed in order to increase in the people income in the coastal areas of Southeast Maluku Regency.